Global Challenges in Water Governance : Environments, Economies, Societies - J. Schmidt, Jeremy; Matthews, Nathanial (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book presents a historically situated explanation of the rise of global water governance and the contemporary challenges that global water governance seeks to address. It is particularly concerned with connecting what are often technical issues in water management with the social and political structures that affect how technical and scientific advice affects decisions. Schmidt and Matthews are careful to avoid the pitfalls of setting up opposing binaries, such as 'nature versus culture' or 'private versus public', thereby allowing readers to understand how contests over water governance have been shaped over time and why they will continue to be so. Co-written by an academic and a practitioner, Global Challenges in Water Governance combines the dual concerns for both analytical clarity and practical applicability in a way that is particularly valuable both for educators, researchers, decision-makers, and newcomers to the complexities of water use decisions.
Keywords: Social sciences.; Environmental management.; Water pollution.; elektronické knihy; electronic books